2016
DOI: 10.1016/j.expneurol.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Physiological cerebrovascular remodeling in response to chronic mild hypoxia: A role for activated protein C

Abstract: Activated protein C (APC) is a serine protease that promotes favorable changes in vascular barrier integrity and post-ischemic angiogenic remodeling in animal models of ischemic stroke, and its efficacy is currently being investigated in clinical ischemic stroke trials. Interestingly, application of sub-clinical chronic mild hypoxia (CMH) (8% O2) also promotes angiogenic remodeling and increased tight junction protein expression, suggestive of enhanced blood-brain barrier (BBB) integrity, though the role of AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…and that this is associated with upregulated expression of fibronectin and its receptor α5β1 integrin on spinal cord blood vessels (Boroujerdi et al, 2013). In a different model, we showed that chronic mild hypoxia stimulates angiogenic remodeling and interestingly found that APC appears to plays a key role in mediating this response, as functional blockade of APC prevented both upregulation of the fibronectin-α5β1 integrin axis and the associated angiogenic response, while in contrast, exogenous APC enhanced this response (Burnier et al, 2016). In light of these findings, we wondered if the protective effect of APC in EAE might be due to enhanced fibronectin-α5β1 integrin signaling driving a stronger angiogenic response.…”
Section: Apc Treatment Has No Discernible Influence On Angiogenic Remmentioning
confidence: 81%
See 2 more Smart Citations
“…and that this is associated with upregulated expression of fibronectin and its receptor α5β1 integrin on spinal cord blood vessels (Boroujerdi et al, 2013). In a different model, we showed that chronic mild hypoxia stimulates angiogenic remodeling and interestingly found that APC appears to plays a key role in mediating this response, as functional blockade of APC prevented both upregulation of the fibronectin-α5β1 integrin axis and the associated angiogenic response, while in contrast, exogenous APC enhanced this response (Burnier et al, 2016). In light of these findings, we wondered if the protective effect of APC in EAE might be due to enhanced fibronectin-α5β1 integrin signaling driving a stronger angiogenic response.…”
Section: Apc Treatment Has No Discernible Influence On Angiogenic Remmentioning
confidence: 81%
“…Based on our previous findings that during the presymptomatic phase of EAE, a marked vascular remodeling response occurs (Boroujerdi et al, 2013), and that APC plays a key role in mediating cerebrovascular remodeling in response to chronic mild hypoxia (Burnier et al, 2016), we wondered if the protective effect of APC in EAE might, in part, be the result of upregulated fibronectin-α5β1 integrin signaling driving an enhanced angiogenic response. However surprisingly, APCtreated mice showed no appreciable differences in their vascular expression of fibronectin or α5β1 integrin or their overall level of vascularity, compared to vehicle-treated control mice.…”
Section: The Impact Of Apc On Vascular Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism might not be so simple since other factors are no less important. For instance, the accumulation of protein C in the brain tissue in the postischemic period stimulates endothelial proliferation, increases vascular density, and activates pro-angiogenic integrins α5β1 and avβ3 [ 27 ]. In parallel, protein C suppresses apoptosis of brain endothelial cells in ischemia [ 28 ], thereby preventing the reduction of the capillary bed.…”
Section: General Mechanisms Of Microvasculature Remodelingmentioning
confidence: 99%
“…54 APOε4 mice have a permeable BBB which can be reversed by inhibiting the pro-inflammatory cyclophilin A pathway 55 ; however, inhibitors of cyclophilin A have yet to materialize into the clinical arena. Also, activated protein C can also improve endothelial barrier integrity 56 ; again, this information has yet to be translated into clinical utility.…”
Section: Restoring the Bbbmentioning
confidence: 99%